The Balance Metabolism Safety Net: Integration of Stress Signals by Interacting Transcriptional Factors in Streptomyces and Related Actinobacteria - Martín, Juan F.; Liras, Paloma (Frontiers in Microbiology, 2020)
Soil dwelling Streptomyces species are faced with large variations in carbon or nitrogen sources, phosphate, oxygen, iron, sulphur and other nutrients. These drastic changes in key nutrients result is an unbalanced metabolism that have undesirable consequences for growth, cell differentiation, reproduction and secondary metabolites biosynthesis. In the last decades evidence has accumulated indicating that mechanisms to correct metabolic unbalances in Streptomyces species take place at the transcriptional level, mediated by different transcriptional factors. For example, the master regulator PhoP and the large SARP-type regulator AfsR bind to overlapping sequences in the afsS promoter and, therefore, compete in the integration of signals of phosphate starvation and S-adenosylmethionine concentrations. The cross-talk between phosphate control of metabolism, mediated by the PhoR-PhoP system, and the pleiotropic orphan nitrogen regulator GlnR, is very interesting; PhoP represses GlnR and other nitrogen metabolism genes. The mechanisms of control by GlnR of several promoters of ABC-type sugar transporters and carbon metabolism are hightly elaborated. Another important cross-talk that governs nitrogen metabolism involves the competition between GlnR and the transcriptional factor MtrA. GlnR and MtrA exert opposite effects on expression of nitrogen metabolism genes. MtrA, under nitrogen rich conditions, represses expression of nitrogen assimilation and regulatory genes, including GlnR, and competes with GlnR for the GlnR binding sites. Strickingly, these sites also bind PhoP. Novel examples of interacting transcriptional factors, discovered recently, are discussed to provide a broad view of this interactions. Altogether, these findings indicate that cross-talks between the major transcriptional factors protect the cell metabolic balance. A detailed analysis of the transcriptional factors binding sequences suggests that the transcriptional factors interact with specific regions, either by overlapping the recognition sequence of other factors or by binding to adjacent sites in those regions. We propose to define the signal integration DNA regions (so called integrator sites) that assemble responses to different stress, nutritional or environmental signals. These integrator sites constitute nodes recognized by two, three or more transcriptional factors to compensate the unbalances produced by metabolic stresses. This interplay mechanism acts as a safety net to prevent major damage to the metabolism under extreme nutritional and environmental conditions.